Development Of Production-Based Learning Models For Optimizing The Technopreneurship Spirit In Higher Education - Idi Jang Cik (Green Publisher Indonesia, 2021)
Development of production-based learning models carried out to seek validity, practicality and effectiveness in the application of technopreneur courses in universities. Production-based learning model is an alternative to develop students' skills, attitudes and knowledge that are relevant today. Research and development is used to test the validity of experts through Focus Group Discussions (FGD), then limited trials are carried out in the development of this production-based learning model. From the processes carried out, a new syntax development is produced which refers to the previous model syntax. The development of the syntax sequence is (1) an analysis of the curriculum and characteristics of students; (2) Product identification and analysis; (3) Make important questions about the product; (4) Question mapping; (5) analysis of equipment and materials needed for the product to be made; (6) create a business plan (7) product manufacturing process; (8) small-scale operations that include promotion and sales, (9). Summative evaluation; From the stages of the research carried out, the resulting Aiken's V value is 0.812 with a valid category, while the calculation of the Effectiveness value gets the results of 82.22 (effective) and Practicality of 89.33 (very practical). So it can be said that the production-based learning development model has validity, practicality and effectiveness values ​​that meet the requirements, so it is feasible to apply.